Numerical Study of the Effect of the Location of Baffles on the Flow and Heat Transfer of A Newtonian Fluid in A Ventilated Enclosure - Boutra Abdelkader (EDP Sciences, 2021)
Flow and heat transfer analysis in ventilated cavities is one of the most widely studied problems in thermo-fluids area. Two-dimensional mixed convection in a ventilated rectangular cavity with baffles is studied numerically and the fluid considered in this study is hot air (Pr = 0.71). The horizontal walls are maintained at a constant temperature, higher than that imposed on the vertical ones. Two very thin heat-conducting baffles are inserted inside the enclosure, on its horizontal walls, to control the flow of convective fluid. The governing equations are discretized using the finite volume method and the SIMPLER algorithm to treat the coupling velocity–pressure. Line by line method is used to solve iteratively the algebraic equations. The effect of the Richardson number Ri (0.01- 100) and the location of the baffles within the cavity on the isothermal lines, streamlines distributions and the average Nusselt number (Nu) has been investigated. The result shows that the location opposite the baffles, close to the fluid outlet, is the optimal choice to be considered for industrial applications.